2017
DOI: 10.1038/s41598-017-09201-5
|View full text |Cite
|
Sign up to set email alerts
|

Precise stacking of decellularized extracellular matrix based 3D cell-laden constructs by a 3D cell printing system equipped with heating modules

Abstract: Three-dimensional (3D) cell printing systems allow the controlled and precise deposition of multiple cells in 3D constructs. Hydrogel materials have been used extensively as printable bioinks owing to their ability to safely encapsulate living cells. However, hydrogel-based bioinks have drawbacks for cell printing, e.g. inappropriate crosslinking and liquid-like rheological properties, which hinder precise 3D shaping. Therefore, in this study, we investigated the influence of various factors (e.g. bioink conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
120
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 42 publications
1
120
0
Order By: Relevance
“…Natural hydrogels have been generated from, e.g. decellularized human adipose (20), heart (15), and liver (17) tissue and more (1,9,23,25). As for the lung, hydrogels have been generated from porcine lung ECM (22).…”
Section: Introductionmentioning
confidence: 99%
“…Natural hydrogels have been generated from, e.g. decellularized human adipose (20), heart (15), and liver (17) tissue and more (1,9,23,25). As for the lung, hydrogels have been generated from porcine lung ECM (22).…”
Section: Introductionmentioning
confidence: 99%
“…dECM bioinks only require the maintenance of ECM composition and therefore tissue and organs can be cut, sliced or ground into small pieces [75,76]. The pieces are then exposed to decellularization agent with shaking for different periods of time ranging from hours to days and sometimes weeks [14,42,52,73,77]. In addition, cutting or slicing tissue or organ into small pieces allows the process of decellularization to be done in a short time due to increased surface area [73].…”
Section: Decellularization Methodsmentioning
confidence: 99%
“…In addition, the dECM bioink was able to enhance the formation and maturation of myotubes than a collagen bioink and responded well to electrical stimulation [106]. Ahn and co-workers derived dECM bioink from porcine skin tissues, with their method showing the retention of collagen from the native tissue [77]. The authors showed that their method of bioprinting, involving a heating system, did not adversely affect cell viability whilst ensuring gelation of dECM bioink [77].…”
Section: Decellularized Ecm As Bioinkmentioning
confidence: 99%
See 1 more Smart Citation
“…Decellularized tissue or ECM‐based bioink formulations are developing fields due to their ease of printability and their inherent bioactivity (Ji & Guvendiren, ). dECM from cartilage (Pati et al, ), fat (Pati et al, ), heart (Das & Jang, ), skin (Ahn et al, ), and liver (Lee et al, ) has already been used for 3D bioprinting. Further, in the future, dECM from one tissue might be applied for another tissue.…”
Section: Future Prospectsmentioning
confidence: 99%